Teaching and evaluating student writing - Trost, Mary Ann.; McDougal, Littell (Evanston, Ill. : McDougal, Littell & Co., 1984)
Discusses how to improve the teaching of writing in the classroom, how student compositions should be evaluated, and the relation of writing to other studies.
Includes bibliographical references : (pages 45-47).
Keywords: English language -- Composition and exercises; English language -- Study and teaching